Entrepreneurial Influencers: Harnessing History to Guide Contemporary Opportunities - Ndinguri, Erastus; Hill, Jessica (Archives of Business Research, 2024)
This research utilizes management and entrepreneurial philosophies from Robert S. Abbott to highlight the life and accomplishments of an early influencer and the principles that contributed to his entrepreneurial success. In addition to exploring the influence of an early figure, the study employs essential pedagogy to develop an initial model that formulates a value proposition rationale for contemporary social media influencers who seek to leverage their influence for entrepreneurial gain.